{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# hw7-sol - AMS 311(Fall 2010 Joe Mitchell PROBABILITY THEORY...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: AMS 311 (Fall, 2010) Joe Mitchell PROBABILITY THEORY Homework Set # 7 – Solution Notes (1). (15 points) (a). If E (3 X ) = var ( X/ 2) and var (2 X ) = 3 , find (i). E [(2 + X ) 2 ] and (ii). var (4 + 3 X ) . If E (3 X ) = var ( X/ 2) = (1 / 4) var ( X ) and 3 = var (2 X ) = 4 var ( X ), then we know that var ( X ) = 3 / 4 and E ( X ) = (1 / 3)(1 / 4) var ( X ) = 1 / 16. Thus, since var ( X ) = E ( X 2 )- [ E ( X )] 2 , we know that 3 / 4 = E ( X 2 )- [1 / 16] 2 , so E ( X 2 ) = 193 / 256. Thus, E [(2 + X ) 2 ] = E [4 + 4 X + X 2 ] = 4 + 4 E ( X ) + E ( X 2 ) = 4 + 4 · ( 1 16 ) + 193 256 = 1281 256 and var (4 + 3 X ) = 3 2 var ( X ) = 9 · (3 / 4) = 27 / 4 (b). Suppose that X and W are independent and that var ( W ) = 7 , E (( X- W )( X + W )) = 100 , E (3 W ) = 30 , E ( X 3 ) = 60 , and E ( X + W ) = 12 . Compute (i) var ( X ) and (ii) cov ( X 3 ,W 2 ) . We are told that E (3 W ) = 30; thus, E (3 W ) = 3 E ( W ) = 30, so E ( W ) = 10. We are told that E ( X + W ) = 12; thus, E ( X + W ) = E ( X ) + E ( W ) = E ( X ) + 10 = 12. So we conclude that E ( X ) = 2. We are told that var ( W ) = 7; thus, var ( W ) = E ( W 2 )- [ E ( W )] 2 = E ( W 2 )- 10 2 = 7, so we conclude that E ( W 2 ) = 107. We are told that E (( X- W )( X + W )) = 100; thus, E (( X- W )( X + W )) = E ( X 2- W 2 ) = E ( X 2 )- E ( W 2 ) = E ( X 2 )- 107 = 100, so we know that E ( X 2 ) = 207. This tells us that var ( X ) = E ( X 2 )- [ E ( X )] 2 = 207- 2 2 = 203. We now compute cov ( X 3 ,W 2 ) = E ( X 3 · W 2 )- E ( X 3 ) E ( W 2 ). Now, by independence of X and W , we know that E ( g ( X ) h ( Y )) = E ( g ( X )) E ( h ( Y )). Thus, cov ( X 3 ,W 2 ) = E ( X 3 · W 2 )- E ( X 3 ) E ( W 2 ) = E ( X 3 ) E ( W 2 )- E ( X 3 ) E ( W 2 ) = 0. (In fact, since X and W are independent, we see that cov ( g ( X ) ,h ( Y )) = 0 for any functions g and h .) (2). (15 points) The random variables X and Y have a joint density function given by f ( x,y ) = braceleftbigg 2 e- 2 x /x if ≤ x < ∞ , ≤ y ≤ x otherwise Compute cov (2 X,Y + 3) ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 4

hw7-sol - AMS 311(Fall 2010 Joe Mitchell PROBABILITY THEORY...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online